Kontribusi Pemahaman Hadis dalam Memahami Hukum Cryptocurrency - Wijaksana, Muhammad Aditya; Faishal, Muhammad (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2025)
The study of cryptocurrency law from an Islamic perspective presents an epistemological challenge that demands a deep understanding of the hadith as one of the primary sources of Sharia law. The increasing use of digital assets such as Bitcoin and Ethereum, coupled with the controversy surrounding their halal-haram status, has created a need to explore the contribution of hadith understanding in framing the legality of cryptocurrency. This study aims to analyze how understanding hadith, both textually and contextually, can provide a normative basis for legal assessments of digital assets. Using qualitative methods with a thematic and hermeneutic approach, this study examines hadith related to the principles of muamalah (muamalah), such as the prohibitions on gharar (unlawful exchange), riba (usury), and maisir (investment), as well as the concepts of justice and clarity of contracts. The research findings indicate that understanding hadith cannot be applied literally but requires reinterpretation based on maqāṣid al-Sharī‘ah (the principles of Islamic law) to address the realities of the digital economy. Hadiths on riba-based exchange and the obligation to clarify exchange rates provide an ethical framework for cryptocurrency transaction mechanisms, while hadiths on trustworthiness and asset protection reinforce the urgency of regulation and transparency. This research reveals that cryptocurrency law is highly dependent on its usage characteristics: it can be considered legitimate as a medium of exchange if it meets the requirements of fairness, clarity, and freedom from excessive speculation, but is potentially prohibited if it dominates speculative and manipulative practices. The implications of this research emphasize the importance of developing contemporary ijtihad based on hadith to formulate guidelines for digital economic fiqh, enabling religious authorities to issue fatwas that are adaptive and responsive to modern financial innovations.